Developing better treatments in hepatocellular carcinoma. (October 2010) - Duffy, Austin; Greten, Tim
The marked heterogeneity of hepatocellular carcinoma (HCC), particularly with regard to the etiology and severity of the underlying cirrhosis, makes clinical trial design in this disease very challenging. In addition, despite the global burden of HCC, there have been relatively few randomized studies. The major advance in medical therapy in HCC has been the benefit of sorafenib, as demonstrated in two Phase III studies. However, the benefit is small, and new therapies to augment or replace sorafenib are urgently needed. These newer therapies, as well as the progress made in two important areas – clinical trial design and molecular characterization – are the subject of this article.